THE ROLE OF LEADERSHIP IN TEACHERS’ SELF-EFFICACY - Mammadzada, Mirali (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
The self-efficacy of teachers is an important aspect that must be considered in evaluating educational systems. It is affected by several factors such as teachers’ professional development, motivation, and satisfaction. These factors are in turn, affected by leadership roles in the educational system. This paper aimed to determine the correlation between the role of leadership and teachers’ self-efficacy through these factors. A qualitative approach was used where secondary analysis of written articles was conducted. The demographic of the sample in each journal article studied included primary, secondary, and tertiary schoolteachers in Europe. Results show that the factors under study are affected by the leadership roles of principals, school administrators, and teachers. Leadership roles improve teachers’ professional development, boost motivation, and increase job satisfaction which as a result, affects the self-efficacy of teachers. Thus, the leadership roles of principals, school administrators, and teachers, particularly a transformational type of leadership in contrast with a transactional form of leadership, affect the self-efficacy of teachers positively and ultimately their performance in their classes.